11 Reducing the severity of stroke. (December 2018) - Rudd, Anthony
Abstract : 100 000 people in the UK have a stroke and worldwide it is responsible for 15 million deaths every year. With the ageing population, it is predicted that mortality will rise by 45% over the next 20 years in Europe and there will be over 4.5 million stroke survivors. Only 30 years ago it was considered to be a largely untreatable disease. There was no evidence for any acute intervention and rehabilitation was sporadic and rarely available at all in the community. In fact, little had changed over the previous century since Osler had written that 'there was no possibility of a cure'. Huge advances have been made in reducing the severity of stroke. Being managed on a stroke unit compared to a general ward reduces the odds ratio of death or dependency by 21%. Intravenous thrombolysis does not save lives but overall greatly increases the chance of disability free survival. The last 3 years has seen publication of multiple trials of thrombectomy, all showing major benefits in reducing disability. Transferring patients from hospital to home early, continuing specialist rehabilitation and early supported discharge team are also more effective than conventional care at reducing the severity of stroke. Delivering evidence based care to all patients regardless of where they live and when they have a stroke is challenging. Progress is being made with stroke being a priority area for the NHS, learning the lessons from the restructuring of stroke services in London and Manchester.